Tinjauan Kebutuhan Tenaga Kerja Petugas Rekam Medis Berdasarkan Metode Workload Indicator of Staffing Needs (WISN) di Klinik Rawat Inap Ramdani Husada - Irma Wulandari; Fitri Indahsari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The medical record is one of the most important parts of a health service which must be supported by an adequate number of human resources, so it is necessary to calculate the exact workforce requirements. Medical record activities at Ramdani Husada Inpatient Clinic are not done by officers with medical record education qualifications but are carried out by officers with qualifications of high school education, midwifery diploma, and midwifery diploma. The research objective was to describe the need for medical record personnel based on the WISN (Workload Indicator of Staffing Need) method at the Ramdani Husada Inpatient Clinic. The research design used descriptive quantitative with a cross-sectional approach. The population and sample of the study were all officers who carried out medical record activities as many as 3 people including the clinic manager, head of administration, and administrative staff. The results showed that the available work time was 1,953 hours/year or equivalent to 117,180 minutes/year, the workload standard was not in accordance with the number of available officers, the allowance standard was 1.70 workers. So that the need for medical record officers based on the WISN method is 9 workers. Based on the research results, there is a gap between theory and practice, where the Ramdani Husada Inpatient Clinic does not use the WISN method or other methods for planning its workforce. It is suggested that the Ramdani Husada Inpatient Clinic do deeper planning related to the workforce, especially for medical record officers to increase work productivity and reduce the risk of fatigue in officers.